2017
DOI: 10.1590/1806-90882017000100014
|View full text |Cite
|
Sign up to set email alerts
|

ASSESSMENT OF GENETIC STABILITY OF MICROPROPAGATED Eucalyptus globulus Labill HYBRID CLONES BY MEANS OF FLOW CYTOMETRY AND MICROSATELLITES MARKERS

Abstract: -Flow cytometry and microsatellite markers were used to determine a genetic fidelity of micropropagated plants from the two Eucalyptus urophylla x E. globulus clones and a Eucalyptus grandis x E. globulus clone derived from adult material. Clones were repeatedly subcultured for 25 subcultures on MS medium supplemented with BA (2.22 µM) and ANA (0.05 µM) for in vitro shoot multiplication. The elongation was performed in MS culture medium supplemented with AIB (2.46 µM) and BA (0.22 µM). The ex vitro rooting and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
1
0
0
Order By: Relevance
“…europaea var. sylvestris [39], Eucalyptus globulus [45], Neolamarkia cadamba [46], and Disanthus cercidifolius [47]. In this study, the histogram obtained from the leaf nuclei of the in vitro plants and the donor plants revealed that the fluorescence peaks of all of the samples were consistent, indicating that the ploidy level of the regenerated plants was maintained, thereby ensuring the efficacy this protocol plant without compromising its genetic integrity.…”
Section: Discussionsupporting
confidence: 51%
“…europaea var. sylvestris [39], Eucalyptus globulus [45], Neolamarkia cadamba [46], and Disanthus cercidifolius [47]. In this study, the histogram obtained from the leaf nuclei of the in vitro plants and the donor plants revealed that the fluorescence peaks of all of the samples were consistent, indicating that the ploidy level of the regenerated plants was maintained, thereby ensuring the efficacy this protocol plant without compromising its genetic integrity.…”
Section: Discussionsupporting
confidence: 51%